Introduction to thinking place: Materiality, atmospheres and spaces of belonging. (October 2022) - la Fuente, Eduardo de; Gibson, Margaret; Walsh, Michael James; Szypielewicz, Magdalena
This introduction positions the special issue by highlighting the inherent relationality of place as well as how place is not just an object of analysis but something that shapes thinking, writing and experiences of the world. We reflect on why sociology has found it somewhat more difficult than its social science counterparts to give place the centrality it merits, and discuss whether this reflects a problem with dealing with questions of 'scale' and thinking the 'in-betweenness' of place. We assess important formulations of place in recent place theories, including non-essentialist framings of place such as 'progressive' and as 'assemblage'. We make a case for seeing the articles in this special issue (and Thesis Eleven 's own long history of publishing writing on the topic of place) as resonating with the themes of place as materiality, atmospheres and spaces of belonging.